The uselessness of using salivary microbiota in forensic identification purposes of a person with recent antibiotic use - Karadayi, Beytullah; Karaismailoglu, Bedri; Karadayi, Sukriye; Arslan, Ali; Gozen, Emine Deniz; Ozbek, Tulin (ELSEVIER IRELAND LTD, 2024)
The detection of microbial flora changes in saliva samples because of antibiotic use through advanced molecular genetic analysis is important for forensic and clinical applications. This study aims to reveal the variability in the microbial structure of human saliva after antibiotic use with metagenomic analysis techniques from a forensic point of view. Within the scope of the study, saliva samples were collected from patients who were under the effect of regional anesthesia to be administered a standardized course of antibiotic therapy that lasted for a week. The analysis was conducted on 56 saliva samples from 14 individuals over four different time intervals. Isolation of the 16S rRNA region and PCR analysis were performed prior to sequence analysis to determine the microbiome structure of the samples at phylum, genus, and species levels. As expected, changes were observed in bacterial species found in saliva samples after administration of antibiotics and this was linked to the specific type of antibiotics that were administered. This change was statistically significant for Firmicutes, Spirochetes, and Verrucomicrobiota. Furthermore, although the oral microbiome tends to return to its former state at the phylum and genus level within a 4-week period after the start of antibiotic use, it is observed that the change, especially in some bacterial species, still continues. The findings of this study show that because of the inability of stabilization at species-level in a period of 4 weeks from the start of antibiotic use, it is not suitable to assess saliva samples at species-level for forensic identification.
Keywords: Forensic identification; Saliva microbiome; Metagenomic analysis; Antibiotic; BACTERIAL COMMUNITY; DIVERSITY; Legal Medicine; Biomedical Social Sciences